2015
DOI: 10.1017/jie.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Language Speaking Students Learning Mathematics in English: Expectations of and for Teachers

Abstract: Effective mathematics teaching for Indigenous language speaking students needs to be based on fair expectations of both students and teachers. Concepts of 'age-appropriate learning' and 'school readiness' structure assessment expectations that entire cohorts of Indigenous language speaking students are unable to meet. This institutionalises both student and teacher failure, as both are exhorted to meet unachievable expectations. The voices of teachers teaching in a very remote school provide insight into teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…The teachers in Edmonds-Wathen (2015) reported challenges from the need for a shared language before adding new mathematical language, and the difficulty in distinguishing the effects of language issues in a complex situation. We show these issues are relevant in a second dialect acquisition setting, where language learning needs can be invisible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The teachers in Edmonds-Wathen (2015) reported challenges from the need for a shared language before adding new mathematical language, and the difficulty in distinguishing the effects of language issues in a complex situation. We show these issues are relevant in a second dialect acquisition setting, where language learning needs can be invisible.…”
Section: Discussionmentioning
confidence: 99%
“…Remarks from teachers quoted in a recent study (Edmonds-Wathen, 2015) express their experiences of this in a multilingual community in the remote Northern Territory, where several Indigenous languages are spoken (Edmonds-Wathen, 2015, p. 51), but where Standard Australian English (SAE) 1 is the language of both teaching and educational materials at school. One teacher, for example, stressed the importance of sharing the language of instruction with students, but found that the extra ‘leap forward’ to new mathematics language and concepts was difficult without a shared language.…”
mentioning
confidence: 99%
See 3 more Smart Citations